Risk management as a success factor in the international activity of Spanish engineering - Alicia Lozano-Torró; Tatiana García-Segura; Laura Montalbán-Domingo; Eugenio Pellicer (Administrative Sciences, 2019)
During the period between 2008-2013, the internal market in Spain was characterized by economic crisis, the contraction of the demand experienced in a turbulent business environment, and strong competition among companies. This situation forced many of these companies to work abroad. One of the success factors for Spanish engineering companies abroad has been effective risk management, which avoids compromising the company's objectives, market share, or survival. This article examines the importance of risk management in the success of Spanish engineering consulting firms in the international construction market. Ten executives of Spanish engineering companies with international experience were interviewed, analyzing the importance of risk management for them in the success of internationalization compared with other success factors. The results show that the size of the companies interviewed has no influence on the importance that they gave to risk management, but international experience does relate to the assessment of risk identification and management as a success factor. In addition, companies considered risk management a key factor for optimizing their performance in foreign markets.
Keywords: 350; Spanish engineering companies; international market; risk management; success factors